An improved methodology to screen genotypes of Brachiaria spp for resistance to spittiebug (Homoptera: Cercopidae) in greenhouse conditions - SOTELO, GUILLERMO; CARDONA, CÉSAR; MILES, JOHN (Revista Colombiana de Entomología, 1998)
A new methodology to evaluate genotypes of Brachiaria spp for resistance to the spittlebug Aeneolamia varia E (Homoptera: Cercopidae) is described and supported. The methodology proposed herein allows precise identification of genotypes possessing antibiosis to nymphs, tolerance to nymphs and adults, and combinations of these mechanisms. Apart from being precise in the evaluation of Brachiaria genotypes for resistance or susceptibility to spittlebug, the new methodology is 50% faster, requires 70% less greenhouse space, and 70-80% fewer material resources. It permits the evaluation of nymphal damage to the plants (which was not possible with previously used methodologies) and to increase the number of genotypes screened per year from 300 to 2,000. It does not have contamination problems and may be used with other spittlebug species.